A policy analysis of China’s sustainable rural revitalization: integrating environmental, social and economic dimensions - Guo, Yi; Li, Shengchao (Frontiers in Environmental Science, 2024)
Rural decline has become a global challenge threatening sustainable development. Many countries have explored rural revitalization strategies, but systematic research on policy mechanisms and optimization paths is lacking. This study collected 74 rural revitalization policy texts in China from 2018 to 2024 through stratified sampling. Combining qualitative coding and quantitative modeling, including grounded theory, LDA topic model, sentiment analysis and semantic network analysis, this study constructed an integrated analytical framework to examine policy themes, emotional expression and logical relationships. The results identified the "Five Revitalizations" framework focusing on industrial, talent, cultural, ecological and organizational revitalization, as well as the "Four Supports" of institutional innovation, input guarantee, technological support and legal protection. The policy texts exhibit an increasingly optimistic tone, with traditional themes of deepening rural reform and increasing agricultural investment coexisting with emerging themes of urban-rural integration and digital countryside construction. Semantic network analysis further revealed the intrinsic linkages among policy themes. Comparative analysis with international rural revitalization cases yielded the following optimization paths: improving urban-rural integration mechanisms, strengthening diversified input guarantee, enhancing technological and talent support, and innovating rural governance models. This study enriches the theoretical understanding and practical guidance for sustainable rural revitalization from a global perspective.